Improvement of individual issues regarding accounting methodology - V.V. Yasyshena (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Constant changes in the economy and other spheres of social development, respectively, cause changes in the accounting system, which requires appropriate improvement of its methodology. The following approaches to the construction of accounting methodology are considered: procedural, additive, a combination of procedural and additive approaches, systemic. It is noted that the accounting methodology requires transformation based on a systematic approach. It is recommended to review the composition and procedure of accounting principles and financial reporting in domestic and international legal documents. The expediency of wider disclosure of the principles of accounting and financial reporting in the Law of Ukraine «On Accounting and Financial Reporting in Ukraine» and in the NP(S)A 1 «General Requirements for Financial Reporting» is substantiated. The necessity of outlining the principles in the following composition and order is substantiated: autonomy, sequence, documentary confirmation, full coverage, prudence, continuity, accrual, and the prevalence of essence over form, historical (actual) cost, a single monetary unit of measurement, periodicity, rationality, communication, reduction of entropy (disorder). It is emphasized that the principles of rationality, documentary confirmation, communication, reduction of entropy (disorder), which will contribute to improving the quality of information formation and are an objective basis that influences all elements of the accounting method, should be additionally taken into account when conducting accounting and preparation of financial statements. The differences in presentation of principles in domestic and international legal documents, which are different sets, the essence of the recommended principles and their number, are emphasized. The interrelation between additive and procedural approaches is disclosed through the disclosure of accounting procedures and the totality of elements of the accounting method based on the relevant accounting principles.